Representation Of The Evolution Of The Social Function Of Aesthetic Coffee Shop Among Gen Z In Pontianak City - Mutiara; Kayla Andreyani; Mentari (CV Edujavare Publishing, 2026)
Aesthetic coffee shops have become popular social spaces for Generation Z in Pontianak. The city was selected as the research site due to Gen Z's high level of enthusiasm for coffee culture and coffee shop visits—activities that have evolved from mere consumption into an integral part of their daily lifestyle. This phenomenon is driven by the rapid emergence of new coffee shops featuring compelling visual and aesthetic concepts, positioning Pontianak as a city with a vibrant